Effect of School-Based Interventions on Body Mass Index Among Adolescents: A Systematic Review and Meta-Analysis - Munusamy, Gomathi; Shanmugam, Ramesh (National Journal of Community Medicine, 2022)
Background: High body mass index is a common well-known issue among adolescents, its related morbid-ity track to adulthood life and decrease life expectancy. The review aims to derive a consensus on school-based intervention on body mass index. Objective: This review evaluates the effect of school-based inter-ventions in reducing or preventing high body mass index for adolescents. Method: A literature search was performed in six electronic databases: Pubmed, Science Direct index, Sci-Hub, HINARI, and Google Scholar to identify published studies between January 2010 and December 2020. Only randomized controlled studies evaluated the effect of physical activity and/or physical education and nutritional education and/or dietary behavior, sedentary behavior outcome reporting on body mass index among adolescents were included. The Standard Cochrane tool was used to assess the risk of bias for indi-vidual studies. An evaluation of the effects of included interventions on body mass index was done using a random effects model. Results: There were 6 trials included. 2503 adolescent partakers met the inclusion criteria. Meta-analysis showed there is a significant difference between length of intervention between 3 to 12 months were MD -0.44 kg [95% CI: 1.06, 0.18], p-value = 0.04, with evidence of substantial study between heterogeneity (I2 = 61%). Discussion: Intervention less than three to twelve months more effective with multiple school-based inter-ventions among adolescents. Numerous studies are needed for evaluation to determine long-term interven-tion effectiveness targeted on adolescents.